Ketegangan Politik Lokal: Konstruksi Konflik Agama Tanah Papua - IDRUS AL HAMID; IRWAN ABDULLAH; ZAINAL ABIDIN BAGIR (Universitas Muhammadiyah Yogyakarta, 2013)
Local political conflicts become an integral part ofIndonesia. Various cause roots are assumed comefrom a religious dimension, in addition to ethnicity.In cases of Jayapura, Papua, local political dimensionsof the conflict was obviously display as factorsthat religion should be integrating factor, but in factreligion become disintegrating factor. The variouspower of groups interconnect with a religious impulsethat local political tensions grew louder andspread. The aim of this study is to describe analyticallyabout the emergence of a strain on the locallevel in Jayapura Papua in the field of religion. Toelaborate the analysis in this article, the excavationdata through in-depth interviews, focus group discussion,and literature studies or documents on issuesthat occur on local level.KEYWORDS: local politics, Papua, conflict, religion